THE MICRO- AND NANOSECOND DISCHARGES IN GAS BUBBLES FOR WATER DISINFECTION AND PURIFICATION - N. I. Boyko (National Technical University "Kharkiv Polytechnic Institute", 2019)
Purpose. Comparison of electrical circuits of experimental plants for obtaining micro- and nanosecond discharges in gas bubbles in water and comparing the experimental results obtained for disinfecting water using such discharges. Methodology. To obtain high-voltage pulses on the load in the form of a gas bubbles and a layer of water with a frequency of more than 2000 pulses per second, a method of generating micro- and nanosecond pulses using high-voltage pulse generators based on a pulse transformer (PT) according to Tesla, with a transistor opening switch IGBT in the low-voltage part of the circui . A current-limiting resistor with a resistance Rcl = 24 kW is used to protect the transistor switch at microsecond discharges. At nanosecond discharges, a multi-gap spark gap is used to sharpen the front of high-voltage pulses. We used a capacitive voltage divider with a division factor of Kd = 7653 to measure voltage pulses, a shunt with a resistance of Rs = 2.5 W for measuring current pulses. RIGOL DS1102E digital oscilloscope with a 100 MHz bandwidth was used as a recording device. Results. The effect of micro- and nanosecond discharges in gas bubbles on microorganisms was experimentally investigated. It was possible to reduce the biochemical oxygen consumption of water during microsecond discharges, reduce the turbidity of water, and improve its organoleptic qualities. The energy released in a single pulse with microsecond discharges Wµ ≈ 17 mJ, with nanosecond discharges Wn ≈ 7.95 mJ. At nanosecond discharges, complete inactivation of E.coli bacteria was achieved. The disinfecting and purifying action of nanosecond pulses is better compared to microsecond pulses due to an increase in the amplitude of the pulsed voltage up to 30 kV, and a pulsed current of up to 35 A. Originality. The possibility of effective microbiological disinfection of water using nanosecond discharges in gas bubbles at low specific energy consumption has been experimentally shown. Practical value. The obtained experimental results on water disinfection using micro- and nanosecond discharges offer the prospect of industrial application of installations using such discharges for disinfecting and purification wastewater, swimming pools, and post-treatment of tap water.